PSYCHOLOGICAL CHARACTERISTICS OF PERSONALITY IN ELEMENTARY SCHOOL-AGED CHILDREN IN INDONESIA: REVIEW AND IMPLICATIONS - Lestari, Nur'im Septi; Hanurawan, Fattah; Suciptaningsih, Oktaviani Adhi; Nur Imama Iktamalal Itsnain (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: Children are often exposed to various electronic media such as smartphones, tablets, and computers. Purpose: This research aims to understand and analyze the development of elementary school-aged children in Indonesia concerning various factors: cognitive, social, emotional, identity, role, learning abilities, and environmental aspects. Method: The research employs a Systematic Literature Review (SLR) to synthesize findings from multiple studies addressing these developmental factors. Cognitive development underpins learning and problem-solving skills, while social and emotional growth fosters healthy relationships. Result: The research findings reveal that children's identities and roles are shaped by familial, educational, and community influences, with the family, school, and community environments crucially impacting children's personalities and balanced development. Conclusion: Collaboration among stakeholders is essential for fostering holistic growth in children. The family environment significantly influences children's behavior, with parenting styles and values playing pivotal roles. Formal education, besides academic achievement, focuses on moral development, and teachers serve as role models, offering encouragement and creating supportive classrooms. Peer interactions enhance social skills, while media influence and mental health awareness require supervision and support. Additionally, character education and parental involvement are vital in shaping Indonesian children's holistic personalities. In conclusion, a collaborative effort among stakeholders, including families, schools, and communities, is necessary to nurture the comprehensive development of children in Indonesia, addressing cognitive, social, emotional, and environmental dimensions.